Strengthening Electoral Integrity through Anti-Money Politics Villages: A Socio-Legal Study in Bantul Regency - Gugun el Guyanie; Indra Cipta Lestari; Enggar Wijayanto; Lilik Agus Saputro (Universitas Islam Negeri Raden Intan Lampung, 2026)
The issue of money politics itself has been identified as the core problem of election administration in Indonesia, with its pernicious influence contributing to a degradation of order and a reduction in legal consciousness among the community. The establishment of the Anti-Money Politics Village (DAPU) in Bantul Regency is indicative of a community-based legal movement that resists the deeply ingrained transactional culture of politics. The present study analysed the concept and mechanisms of application of DAPU, its effectiveness, and the community's legal culture regarding election fairness. The research method employed is qualitative socio-legal research. The data is sourced from interviews, documentation, and a literature study. In the context of data sampling, the writer employed a purposive sampling method. The writer employed a qualitative descriptive method for data analysis, drawing on the models proposed by Miles and Huberman. The results indicate that: first, Murtigading village was the first to implement the DAPU concept; second, Guwosari village employs a participatory model; and third, Tirtonirmolo village utilises a more formal model supported by the village government. The findings suggest that the efficacy of the DAPU is contingent on societal participation and the involvement of relevant stakeholders. The study indicates that the culture of legal practices is influenced by cultural brokers. The ultimate success of the DAPU concepts demonstrates the necessity of interdisciplinary cooperation between culture, law, and ethics.